The Criminal Penalties for LGBT in a Human Rights Perspective - Dwiyanti, Ita (Semarang State University Undergraduate Law and Society Review, 2021)
LGBT is essentially an unusual behavior of social aberrations. The cause of a person to be LGBT was due to several factors, genetic, hormonal, gender role discomfort, peer group interaction, social. Human rights exist from the day we are born until we die, and the function of human rights to protect all rights including to live and get legal protection. In terms of human rights criminalizing a person is an offense for depriving them of their rights, but if there is a violation that man is doing, of course it is not a violation even though human rights existed from the moment we are born until we die. Court Decision Number 46/PUU-XIV/2016 becomes controversial because it is considered to have legalized LGBT. If read properly Court decision No. 46/ UU-XIV/2016 this Court does not intend to legalize LGBT but more consider the good and bad.